Antibacterial activity of Paederia foetida leaves using two different extraction procedures against pathogenic bacteria - MELDA YUNITA; MORGAN OHIWAL; MUHAMMAD ZEIN ELFITRASYA; HALIDAH RAHAWARIN (Society for Indonesian Biodiversity, 2023)
Abstract. Yunita M, Ohiwal M, Elfitrasya MZ, Rahawarin H. 2023. Antibacterial activity of Paederia foetida leaves using two different extraction procedures against pathogenic bacteria. Biodiversitas 24: 5920-5927. The objective of this study was to compare the effectiveness of the extraction methods between maceration and infundation of Paederia foetida (Linn.) leaves in suppressing the growth of Staphylococcus aureus and Escherichia coli with concentrations of 10, 25, 50, 75, and 100% using the disc-diffusion method. While phytochemical testing was performed by decoction method. The results of this study revealed that the macerated extract was able to inhibit both S. aureus and E. coli at all concentrations with the inhibition zones varied ranging from 5.8 ± 0.85 - 20.43 ± 0.06 mm and 4.9 ± 0.57 - 18.18 ± 0.67 mm, respectively. While the leaf infusion obtained from infundation method was found to be less able to inhibit both pathogenic bacteria (<1 mm). Results of phytochemical testing confirmed the result of inhibitory testing where macerated extract contained alkaloids, saponins, steroids, terpenoids, and tannins, while the leaf infusion only contained alkaloids and terpenoids. It can be concluded that macerated extracts of P. foetida leaves were far more effective in inhibiting the growth of S. aureus and E. coli. The study implies that the leaf extract of P. foetida can be considered and developed into a strong antibacterial in the future through good and appropriate bioprospecting.